Magnetic Fe3O4 nanoparticles for adsorptive removal of acid dye (new coccine) from aqueous solutions - Weng C.-H.; Lin Y.-T.; Yeh C.-L.; Sharma Y.C. (My University, 2025)
The ability of magnetic Fe3O4 nanoparticles (MFN) to remove new coccine (NC), an acidic dye, from aqueous solutions was studied. Parameters including ionic strength, pH, and temperature were evaluated. MFN, prepared by precipitation method, exhibits an average particle size of 12.5 nm, specific surface area of 85.5 m2/g, and pHzpc of 5.9. Results of kinetic adsorption experiments indicated that the pseudo-second-order rate of adsorption increased with increasing initial NC concentration. Findings also revealed that the equilibrium data could be fitted into Langmuir adsorption isotherm. The adsorption is favored at low pH, high temperature, and low ionic strength, whereupon a maximum adsorption capacity of 1.11 × 10-4 mol/g was determined for NC. Thermodynamic functions indicated that the adsorption process is spontaneous and exothermic in nature. Tests of regeneration showed that after 5 regeneration cycles the adsorption capacity of NC decreased to 35% to its original capacity. © IWA Publishing 2010.